Experimental Research of the Effects of Different Shields on Power Frequency Electric Field Mitigation - Nahman, Jovan; Salamon, Dragutin; Grbić, Maja (Proceedings, Electrical engineering institute "Nikola Tesla", 2012)
The paper describes experimental research on the effects of different shields on power frequency electric field mitigation. This research was performed in order to determine those materials that may be used for electric field mitigation in cases where the reference level is exceeded. Using measured results, the value of the shielding factor has been calculated for all tested shields and the most efficient shields were determined.
Keywords: shielding factor.; electric field strength mitigation; non-ionizing radiation; electric field strength